Resonance characteristics of THz metamaterials based on a drude metal with finite permittivity - Jun, Seung Won; Ahn, Yeong Hwan (Current Optics and Photonics, 2018)
In most previous investigations of plasmonic and metamaterial applications, the metallic film has been regarded as a perfect electrical conductor. Here we demonstrate the resonance characteristics of THz metamaterials fabricated from metal film that has a finite dielectric constant, using finite-difference time-domain simulations. We found strong redshift and spectral broadening of the resonance as we decrease the metal’s plasma frequency in the Drude free-electron model. The frequency shift can be attributed to the effective thinning of the metal film, originating from the increase in penetration depth as the plasma frequency decreases. On the contrary, only peak broadening occurs with an increase in the scattering rate. The metal-thickness dependence confirms that the redshift and spectral broadening occur when the effective metal thickness drops below the skin-depth limit. The electromagnetic field distribution illustrates the reduced field enhancement and reduced funneling effects near the gap area in the case of low plasma frequency, which is associated with reduced charge density in the metal film.
Keywords: Electromagnetic field distribution; Field enhancement; Finite difference time domain simulations; Free electron models; Perfect electrical conductor; Plasma frequencies; Resonance characteristic; Spectral broadening; Metamaterials; Terahertz spectroscopy